ASSESSMENT OF THE QUALITIES OF NEW AROMATIC RICE ACCESSIONS STORED AT FARMERS LEVEL IN BENIN EVALUATION DES QUALITES DES NOUVELLES ACCESSIONS DE RIZ AROMATIQUE STOCKEES EN MILIEU PAYSAN AU BENIN - PAUL A. F. HOUSSOU; VALÈRE DANSOU; ABEL B. HOTEGNI; KOWIOU ABOUDOU; HUGUE ZANNOU; ROSANOFF Y. S. KOUKÈ (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
The objective of this study was to evaluate the physio-chemical and sensorial qualities of five new parfum rice accessions stored under the farmer’s conditions. To do this, five parfum rice accessions ARA-1, ARA-2, ARA-5, ARA-18 and ARA-23 and two control parfum rice varieties (IR 841 and BRIZ 10B) parboiled and not parboiled were packaged in polypropylene bags and then stored for a period of six months by the producers. The physico-chemical, cooking and sensory qualities of the different rice samples were determined at begin storage (T0), three (T1) and six (T2) months storage, using standard methods. The results showed that except for the moisture content and water activity that have slightly increased during storage, the others physico-chemical parameters didn’t vary significantly (p > 0.05) during the storage for non-parboiled and parboiled rice. Processing parameters such as the ease of cooking perceived by processors for the non-parboiled and parboiled rice samples also did not change after six months of storage. The five accessions of non-parboiled rice were pleasantly appreciated by the tasters with ARA-2 the most appreciated followed by ARA-1, ARA-18, ARA-23, and ARA-5. On the other hand, the parboiled ARA-1 and ARA-23 rice accessions were the most appreciated by 90 % of the panelists.